ER Stress Activates the NLRP3 Inflammasome: A Novel Mechanism of Atherosclerosis - Chen, Xinnong (Oxid Med Cell Longev, 2019)
The endoplasmic reticulum (ER) is an important organelle that regulates several fundamental cellular processes, and ER dysfunction has implications for many intracellular events. The nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome is an intracellularly produced macromolecular complex that can trigger pyroptosis and inflammation, and its activation is induced by a variety of signals. ER stress has been found to affect NLRP3 inflammasome activation through multiple effects including the unfolded protein response (UPR), calcium or lipid metabolism, and reactive oxygen species (ROS) generation. Intriguingly, the role of ER stress in inflammasome activation has not attracted a great deal of attention. In addition, increasing evidence highlights that both ER stress and NLRP3 inflammasome activation contribute to atherosclerosis (AS). AS is a common cardiovascular disease with complex pathogenesis, and the precise mechanisms behind its pathogenesis remain to be determined. Both ER stress and the NLRP3 inflammasome have emerged as critical individual contributors of AS, and owing to the multiple associations between these two events, we speculate that they contribute to the mechanisms of pathogenesis in AS. In this review, we aim to summarize the molecular mechanisms of ER stress, NLRP3 inflammasome activation, and the cross talk between these two pathways in AS in the hopes of providing new pharmacological targets for AS treatment.